The parameters of al-ijtihad in zakat: the past and the present - Tahir, Ibrahim Nuhu; Gapur, Oziev (2016)
Throughout the centuries the Muslim Ummah and their scholars in particular have faced questions and challenges about zakat. However, there is a vast difference between raising questions for the sake of seeking knowledge and allegations based on mere assumption rather than on ijtihad. Zakat is a third pillar of Islam and it should therefore be realized that all the rulings and norms related to zakat are fixed by Shari'ah texts which can’t be changed because of change of time and space. To some people certain aspects of zakat seem irrelevant to our contemporary time and therefore they suggest revising the whole concept of zakat and applying it according to our modern era. However, anyone who dares to challenge the established norms of zakat must at least be well versed in the major sources of Shari'ah such as Qur’an, Sunnah, Ijma', Qiyas as well as in Islamic Jurisprudence and the Arabic language. Otherwise what they pose are baseless claims rather than intellectual questions. The authors of this paper focus mainly on three aspects: concept and scope of ijtihad, discussion and responses to various allegations raised by Volker Nienhaus and textual evidences for the proper understanding of zakat. The paper has adopted historical and descriptive methods of analysis.